Legal Politics of Village Fund Supervision in Preventing Potential Corruption in Indonesia - Dewi Ambarwati; Muchammad Ja’far Shodiq (Sociological Jurisprudence Journal, 2025)
Corruption cases related to the misuse of village funds in Indonesia remain a particular problem for the implementation of the village administration system. In fact, even though Indonesia already has regulations regarding the use and supervision of village funds from the government, this has not reduced the potential for corruption in villages. The existence of several abuses of authority by village officials, minimal community participation, and weak internal and external supervision systems for the use of village funds remain the main causes. This study aims to analyze the direction of legal policy on the supervision of village funds in Indonesia, identify obstacles to supervision in practice, and formulate ideal strategies for strengthening the supervision system as a preventive measure against corruption in the village sector. This is a normative legal study using secondary data, analyzed using descriptive and prescriptive analysis. The results of the study indicate that although oversight is regulated normatively, its implementation remains weak due to insufficient oversight capacity, weak integrity of officials, and minimal community involvement. A renewal of legal policy direction is needed, emphasizing the strengthening of oversight based on participation and public transparency.